(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Though always present in Penal Codes, offenses based on belonging to a criminal organization occupy an avant-garde position in today’s evolution of penal law systems:organized crime is located at one of the most outstanding places in the criminal policy agenda. Nevertheless neither criminal law theory, nor the actual content of criminal provisions, nor putting them into practice, enable an adequate restriction.Therefore we need to investigate the wrong doing at the base of this offense. European legal scholarship has proposed two basic approaches: to consider that this offense anticipates the possibility of punishing and prosecuting such behavior (anticipationtheory) or to consider that it harms a collective interest (“public security”, “public peace”). From our perspective, it is necessary to underline the collective wrong doing embedded in a criminal organization and that, beyond the actual crimes committed, it questions the monopoly of violence exercised by the State. It represents the constitution of a violent organization that counters the basis of State political organization (arrogation of political organization). This approach opens a possibility to adequately define the offense of belonging to a criminal organization.